Research Needs to Improve Hypertension Treatment and Control in African Americans. Issue 5 (November 2016) - Whelton, Paul K.; Einhorn, Paula T.; Muntner, Paul; Appel, Lawrence J.; Cushman, William C.; Diez Roux, Ana V.; Ferdinand, Keith C.; Rahman, Mahboob; Taylor, Herman A.; Ard, Jamy; Arnett, Donna K.; Carter, Barry L.; et al.
Abstract : Supplemental Digital Content is available in the text.